Identifikasi Kerusakan pada Hulu Sungai Guo melalui Kegiatan Susur Sungai di Desa Guo Kuranji - Nurhamidah Nurhamidah; Ahmad Junaidi; Rudy Ferial; Masril Syukur; Desry Fitria Marliana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
A river walkthrough is a river activity to see along the watershed, which is carried out to identify the condition of the Guo River and the upstream part of the watershed. The Guo River Walk is one of the community service activities of the Andalas University Research and Community Service Institute (LPPM). This activity was held on September 26, 2021, at the Guo River, Koto Tangah, Kuranji District, Padang City. This activity is also at the same time as World River Day tourism which is celebrated every September 27. The purpose of the river crossing activity, a community service activity, is to identify the type of damage, what factors cause the damage, and the impact caused by the damage to the Guo river and the upstream Guo watershed. This activity was carried out using desk research methods along the river and data analysis. After the Guo River Crossing activity, the community became aware and understood the importance of maintaining a sustainable river for their lives. The author also identified damage to the Guo River and the upstream Guo watershed, including deforested forests due to logging, damage to irrigation canals and river bank landslides due to flooding on August 18, 2021, in Padang. These damages need to be followed up by providing education on the importance of preserving forests for the community and rehabilitating damaged irrigation canals and riverbanks.